2018
DOI: 10.1111/pops.12562
|View full text |Cite
|
Sign up to set email alerts
|

On the Subjectivity of the Experience of Victory: Who Are the Election Winners?

Abstract: Elections represent key moments in democratic countries, and an established finding from the existing literature is that winners of elections display higher levels of satisfaction with democracy. Yet we know almost nothing about the times when voters feel like winners of an election. Using panel data in four countries, this article finds that while the objective performance of the supported party—measured using vote share and changes in vote share from the previous election—has a very important effect on feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…An increase in satisfaction with democracy can be linked to election outcomes through several mechanisms: first, winners might expect to get more utility from the system than losers (in terms for example of implementation of public policies), second, winning can generate positive emotions, and third, winners’ drive for cognitive consistency may motivate them to adjust legitimacy beliefs about the system that supports their political views (Anderson et al., 2005). In this regard, Plescia (2019) found many supporters of parties excluded from government after the elections interpreting the election outcome as a win for their party due to a good showing in the election. The peculiarity of the EP elections is that they are run by national parties within a European arena, which affords both parties and voters the opportunity to proclaim themselves winners if they are the largest party in either the European or the national election competition or have performed well at either one of these two levels.…”
Section: Accepting Electoral Defeat Celebrating Victory?mentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in satisfaction with democracy can be linked to election outcomes through several mechanisms: first, winners might expect to get more utility from the system than losers (in terms for example of implementation of public policies), second, winning can generate positive emotions, and third, winners’ drive for cognitive consistency may motivate them to adjust legitimacy beliefs about the system that supports their political views (Anderson et al., 2005). In this regard, Plescia (2019) found many supporters of parties excluded from government after the elections interpreting the election outcome as a win for their party due to a good showing in the election. The peculiarity of the EP elections is that they are run by national parties within a European arena, which affords both parties and voters the opportunity to proclaim themselves winners if they are the largest party in either the European or the national election competition or have performed well at either one of these two levels.…”
Section: Accepting Electoral Defeat Celebrating Victory?mentioning
confidence: 99%
“… 7 Existing studies on national level elections show that the performance of the voted party compared to the previous election matters in explaining satisfaction with democracy (Plescia, 2019; Stiers et al., 2018). The presence of new national parties (like La République en Marche in France) and the significant changes to EP group membership between 2014 and 2019 render the comparison between the two EP elections not straightforward.…”
mentioning
confidence: 99%
“…This is supported by burgeoning research on voters’ senses of ‘winning’. This research has demonstrated that prior expectations about election outcomes moderate the otherwise large effect of ‘objective performance’ (Plescia, 2019: 1) and that ‘supporters of smaller parties also feel their party won, when and if their party gained votes and seats compared to the previous election’ (Stiers et al, 2018: 21). Van der Meer et al clearly explain the relevance of this to bandwagon research:The definition of success in the opinion polls is a point of discussion by itself, especially in a multiparty context .…”
Section: A Typology Of Bandwagon Effectsmentioning
confidence: 93%
“…The logic behind this baseline expectation is rather straightforward: the better the performance of the supported party, the more likely it is that its voters will feel that their party has won the election and the material and/or emotional ‘payoff’ associated with the experience of victory will translate into higher voter satisfaction for the system in general and specifically for electoral outcomes and the rules leading to that outcome (e.g., Stiers et al. ; Plescia )…”
Section: How and Why Proportionality Mattersmentioning
confidence: 99%